Estudio de redes de baja tensión para reducir el hurto y pérdidas técnicas de energía en el sector de la Coop. Dignidad Popular (sur), mediante la tecnología medidores inteligente “M.I.”. - Maroto Espinoza, Jordan Leonardo (2019)
The present work refers to the study of low voltage networks to determine the amount of theft and technical energy losses that may be found in them, which is why the copp sector has been chosen. Popular Dignity, the purpose is to deduce what are the elements or circumstances that are generating or can generate losses and theft of energy which is affecting considerably in the productive environment and also in the economic to the distributed energy company (CNEL) EP.) The main feature of conducting this research is to study any modality that disturbs the normal operation of a circuit for the distribution of energy which causes inconvenience to customers due to the low voltage they obtain due to the problems that arise in the distribution. of energy. Which have generated a breakdown of the appliances and their malfunctioning of appliances and equipment, due to these the distribution company gets multiple complaints for the dissatisfaction by customers for the service provided.